Pola Komunikasi Interpersonal Orang Tua dan Anak Usia Dini dengan Speech Delay di TK Aisiyah Rewwin Waru - Vevy Liansari (Kanal: Jurnal Ilmu Komunikasi, 2017)
This study aims to know how the pattern of interpersonal communication that occurs between parents and children with speech delay. While the use of this study is as a reference for parents, educators, observers and responsible of education in general in an effort to instill a good example of children and also in an effort to apply good interpersonal communication patterns between both parties. The data collection methods are in-depth interviews and observations. In the process of improving interpersonal communication patterns in parents and children found some obstacles both in the elderly and early age children. The results of this study indicate that the role of parents in establishing interpersonal communication patterns of early childhood greatly affect the behavior of young children. Therefore parents should be able to apply good interpersonal communication patterns to early childhood with speech delay and maintain an intense relationship to reduce the impact of speech delay from internal and external influences.